2011
DOI: 10.1007/s00270-011-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Effects After Multifocal Nonthermal Irreversible Electroporation of the Kidney: Acute and Chronic Monitoring by Magnetic Resonance Imaging, Intravenous Urography and Urinary Cytology

Abstract: This first urographical, urine-cytological, and MRI evaluation after porcine kidney NTIRE shows multifocal parenchyma destruction while protecting the involved urine-collecting system with regenerated urothelial tissue. NTIRE could be used as a targeted ablation method of centrally located renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Indeed, studies have shown that the ablated volumes detected by T1-weighted (T1W), transverse relaxation time (T2), T2-weighted (T2W), fluid attenuated inversion recovery (FLAIR), and diffusion-weighted magnetic resonance imaging (DW-MRI), for the apparent water diffusion coefficient (ADC), are similar to the volumes detected by histological observations. Additionally, T1-Thrive5-3D-GE urogram scans, together with intravenous urography, were used to validate the functionality of NTIRE-ablated swine kidney (161). The usefulness of a particular MRI sequence depends on the type of ablated tissue.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Indeed, studies have shown that the ablated volumes detected by T1-weighted (T1W), transverse relaxation time (T2), T2-weighted (T2W), fluid attenuated inversion recovery (FLAIR), and diffusion-weighted magnetic resonance imaging (DW-MRI), for the apparent water diffusion coefficient (ADC), are similar to the volumes detected by histological observations. Additionally, T1-Thrive5-3D-GE urogram scans, together with intravenous urography, were used to validate the functionality of NTIRE-ablated swine kidney (161). The usefulness of a particular MRI sequence depends on the type of ablated tissue.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Irreversible electroporation (IRE) has been evaluated in multiple preclinical studies (16) for focal ablation of renal parenchyma adjacent to the renal pelvis and the ureter in large animal models. Results from these studies indicate that IRE may be safe for the focal ablation of tissue near such heat-sensitive structures (12).…”
Section: Introductionmentioning
confidence: 99%
“…The oncotherapeutic security of the patient is guaranteed by the inclusion of standard, guideline-compliant tumour resection. IRE is a procedure with potentially attractive characteristics and may be ideal for delivering focal therapy in the kidney, especially as it has been shown to have tissue-selectivity in animal studies that have demonstrated a homogeneous ablation of renal tissue with preservation of larger vessels and the urine-collecting system [6,11,12,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on renal IRE were exclusively experimental or safety-oriented [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A complete histological analysis is still required to assess the completeness of tumour ablation and the nephron-sparing potential of IRE in RCC.…”
Section: Introductionmentioning
confidence: 99%